Agriculture in the western Himalayas – an asset turning into a liability. Issue 2 (17th February 2018) - Shukla, Roopam; Chakraborty, Anusheema; Sachdeva, Kamna; Joshi, P.K.
ABSTRACT: Agriculture in the Himalayas has witnessed dynamic shifts and acute crises over the last decade. This viewpoint identifies and discusses the factors leading to de-agrarianisation and land abandonment in the western Himalayas. Data on farming preferences and bottlenecks for agricultural production were also gathered through a short survey with farmers. Escalating male out-migration, land fragmentation and heightened exposure to uncertain environmental conditions have transformed agriculture into a liability for the farmers. The viewpoint suggests that effective implementation of land consolidation reforms in the region would enhance agricultural production, curtail mass migration, and potentially insulate farmers from the ongoing agrarian crisis.